Makronutrien, kadar air dan kadar abu tepung uwi ungu dengan metode pemotongan menggunakan parut dan pisau slicer - Sunarti, Sunarti; Bintanah, Sufiati sufiati; Safitri, Rosyida Awalia; Marfuah, Dewi; Ulvie, Yuliana Noor Setiawati (Jurnal Gizi, 2024)
ABSTRACT Background: Purple yam is a type of tuber in Indonesia which has the distinctive characteristics of large fruit and purple flesh. The modification of purple yam into a flour product is intended to extend the shelf life and facilitate substitution for product diversification. This research aims to analyze macronutrients consisting of energy, carbohydrates, protein fat, water content and ash content. Method: Experimental research design by dividing uwi based on the cutting method using a grater and slicer knife. Drying using solar temperature. Sieve using a 100 mesh sieve. Fat analysis uses the Soxlet method, protein uses the Kjeidahl method, carbohydrates use the by difference method, water content uses the thermogravimetric method and ash content uses the dry method. Results: The results of the research show that purple yam flour which is cut by grating has an energy content of 320.22 kcal, carbohydrates 77.79%, protein 3.34%, fat 0.70%, water content 8.65% and ash content 3. 88 %. Meanwhile, the cutting method with a slicer knife has an energy content of 321.80 kcal, carbohydrates 78.49%, protein 3.52%, fat 0.5%, water content 9.15 and ash content 3.45. Conclusion: The cutting method using a grater produces higher fat content and ash content, while the cutting method using a slicer knife provides higher carbohydrate, protein, water and energy content. Key words: Macronutrients, water content, ash content, purple yam flour, grated, slicer knife